Ecological risk of imidacloprid on the Brazilian non-target freshwater organisms Chironomus sancticaroli and Poecilia reticulata - Queiroz, Lucas Gonçalves; do Prado, Caio César Achiles; da Silva, Daniel Clemente Vieira Rêgo; Gomes, Luiz Eduardo Thans; Marassi, Rodrigo José; Almeida, Éryka Costa; Pinto, Ernani; da Silva, Flávio Teixeira; de Paiva, Teresa Cristina Brazil (Environmental monitoring and assessment, 2022)
Imidacloprid (IMI) is a neonicotinoid insecticide widely used in agriculture worldwide. This pesticide has been found in freshwater ecosystems, including Brazilian freshwaters. For this reason, studies are being conducted to detect the presence of IMI in freshwater and understand its effects on the aquatic biota. In the present study, the acute toxic effect of the imidacloprid commercial formulation (ICF) Galeão ® on the Brazilian non-target aquatic organisms Chironomus sancticaroli and Poecilia reticulata was evaluated. Enzymatic activities (glutathione S-transferase (GST), catalase (CAT), and ascorbate peroxidase (APX)) were also determined. Moreover, we considered 11 studies that detected IMI concentrations up to 3.65 µg.L −1 in 28 different Brazilian freshwaters to evaluate the acute ecological risk of IMI in these environments. From the ecotoxicological assays, we determined the LC 50 values for C. sancticaroli (LC 50-48 h 1.52 µg.L −1 ) and P. reticulata (LC 50-96 h 122.65 mg.L −1 ). The high sensitivity of C. sancticaroli demonstrates that this species could be used as a bioindicator in studies investigating the contamination of freshwater by IMI. Enzymatic activity changes were observed in both organisms and offered sublethal responses to the effects of the pollution by IMI on aquatic biota. Our results suggest that the presence of IMI in Brazilian aquatic ecosystems can represent a potential ecological risk for the aquatic insect populations and, consequently, cause an imbalance in these ecosystems. The present study provides relevant and comparable toxicity information that may be useful to develop public policies to protect the Brazilian aquatic ecosystem from IMI contamination.